Políticas de infraestrutura energética e capacidades estatais nos BRICS - Carlos Henrique Vieira Santana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Through the concept of state capacity, this study aims to evaluate in comparative way the energy infrastructure policies adopted by Brazil, Russia, India and China (BRIC) in the last twenty years. For this, the article analyze three aspects: the federative dilemmas in coordinating policies, public financing instruments in long-term credit, and bureaucratic cohesion as the mainstay of policy implementation.
Keywords: H11; 330; BRICS; infrastructure; energy; state capacities